An evaluation of the implementation of performance management system : a case study of Ba-Phalaborwa Municipality in Limpopo - Sebashe, Setimela Sampson (My University, 2010)
The purpose of this study was to evaluate the implementation of Performance Management System in the Ba-Phalaborwa Municipality. The need for this study was considered relevant and necessary as municipalities today have become focus points for service delivery as per their constitutional obligations. Central to the constitutional mandate, amongst other things, the Municipal Systems Act 32 of 2000 requires municipalities to establish a Performance Management System that will play a pivotal role in promoting a culture of Performance Management. It is through Performance Management that priorities, objectives and targets set, as contained in the Integrated Development Plan, are implemented and measured. In this study, the researcher evaluates the capacity of the management of the Ba-Phalaborwa Municipality to implement Performance Management System, the compliance of the Performance Management System with legislation and the perceptions of labour unions in the implementation of the Performance Management System. The study further provides an analysis of the state of the Performance Management System in the Ba-Phalaborwa Municipality. It discloses several issues that require immediate attention by management in order to make Performance Management fully compliant and functional. Amongst other things, the study reveals that there is minimal employee involvement in the planning of Performance Management, lack of training opportunities to address identified weaknesses, non-payment of performance bonus to good performing employees and majority of employees not knowing their performance targets as reflected in the Service Delivery and Budget Implementation Plan. The study concludes by providing recommendations to management of the Ba-Phalaborwa municipality on how to enhance good Performance Management. Some of the recommendations proposed are payment of performance bonus to good performing employees, consultations with all employees on the implementation of the system, cascading of the Performance Management to all lower levels employees, to cite just but few examples. The correct implementation of Performance Management System will serve as a means to enhance organizational efficiency, effectiveness and accountability in the use of resources in accelerating access to good quality services and a better life for all.
Thesis (MPA.) -- University of Limpopo, 2010
Keywords: Employee performance; Performance management; Employees, Rating of; Performance standards; Performance -- Management; Work performance standards